TRADITIONAL SINGING IS A UNIQUE ART FORM OF UZBEK MUSIC - Abdullaev Lochinbek Tolibovich (Web of Journals Publishing, 2025)
This article discusses the role and significance of traditional singing in Uzbek music. Singing is studied not only as a performing skill, but also as an art form that expresses the historical, cultural and spiritual values of the people. The article describes the history of the development of traditional singing, its performance styles, techniques in singer performance and various genres (makom, mugham, lyrical songs). It also emphasizes the importance of traditional singing as a cultural heritage and the need for its continuation in modern music. The article draws attention to the artistic aspects of Uzbek music and shows the importance of preserving and developing traditional singing.
Keywords: Traditional singing, Uzbek music, folk songs, vocal art, dutar, tanbur, folk music, musical traditions, singers, modern development.